Evaluation of Midazolam and Ketamine Preceding by Xylazine as General Anesthesia in Rabbits - Ali, Abed F. (The Iraqi Journal of Veterinary Medicine, 2013)
The present study was designed to evaluate the efficacy of use xylazine hydrochloride 5mg/kg BW as premedication and a mixture of midazolam and ketamine 3mg/kg BW, 40 mg/kg BW respectively. The effects of combination was estimated before injection drug as control and each15 min until 90min, on the induction of anesthesia, degree of analgesia, respiratory rate, body temperature and type of recovery. Ten local breed rabbits were used in this study; all animals were done surgical operation (splitting Achilles tenotomy) to evaluated surgical anaesthesia. The result of this combination is reflected good induction of anaesthesia and good analgesia to animals and smooth recovery with miner complication.